Ageing municipalities, gerontocracy and fiscal competition - Anna Montén; Marcel Thum (Center for Economic Studies and ifo Institute (CESifo), 2008)
We develop a simple model of fiscal competition among ageing municipalities. When ageing advances, gerontocracies and social planners gradually substitute publicly provided goods aimed at the mobile young population for publicly provided goods for the elderly. This substitution process does not only depend on the ageing itself but also on crowding effects and on the regional distribution of the elderly population. We show that fiscal competition prevents the exploitation of the young. When the share of the elderly is sufficiently large, the utility of the young is even higher in gerontocracies than in welfare maximizing societies. Due to fiscal competition, the gerontocracies will provide even more of the publicly provided good for the young than the social planner.
Keywords: H4; H7; 330; Demographic change; fiscal competition; publicly provided goods; Öffentliches Gut; Steuerwettbewerb; Finanzföderalismus; Alternde Bevölkerung; Abwanderung und Widerspruch; Theorie